Penerapan Metode Demonstrasi untuk Meningkatkan Hasil Belajar IPA Siswa pada Materi Lingkungan - Sumarni Sumarni; Ramdhan Witarsa; Musnar Indra Daulay (Departement of Mathematics Education, 2022)
This study discusses the learning activities and student learning outcomes of science. the problem that often appears in the science learning process is the low learning outcomes of students who have not reached the school's KKM. This study aims to determine the increase in activity and learning outcomes of third grade students at SD Negeri 027 Rambah in environmental material by applying the demonstration method. This research is a classroom action research carried out in two cycles, each cycle consisting of four stages, namely planning, implementing, observing and reflecting. Reflection is used as a basis for planning improvements in the next cycle. Research data were obtained from observation sheets and learning outcomes tests cycle I and cycle II. The data obtained were analyzed descriptively. The results of this study indicate that the application of the demonstration method can increase student activity and learning outcomes. The increase in student activity from the sufficient category in the first cycle to the good category in the second cycle. The learning outcomes of students who completed the KKM achievement in cycle I were only 13 students (65%), in cycle II it increased to 18 students (75%). Based on the findings of the researchers, it can be concluded that the application of the demonstration method can increase the activity and learning outcomes of science class III students at SD Negeri 027 Rambah.